2021
DOI: 10.1016/j.heliyon.2021.e06086
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and accumulation of Cr in edible parts of Eruca sativa from irrigation water. Effects on polyphenol profile and antioxidant capacity

Abstract: Metals in the environment have been an increasing research topic over the past decade, since they can be found in both natural and drinking water, including irrigation of crops and edible plants with contaminated water. The aim of this study was to investigate the uptake of Cr by arugula ( Eruca sativa ) in a greenhouse experiment, simulating the open field irrigation conditions. We also evaluate the toxic effects of Cr on oxidative stress by measuring the antioxidant capacity and polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
4
1
0
Order By: Relevance
“…Six different flavonoids with high antioxidant ability have been identified in rocket sprouts, from which quercetin reported the highest content followed by kaempferol derivatives (1,2,3, all of them attached to mono- and disaccharide sugars), rutin, and a quercetin derivative (attached to mono- or disaccharide sugars), while kaempferol was found in very low amounts ( Table 3 ), which agrees with those reported by Cuellar et al [ 28 ] and Schiavon et al [ 29 ], who found such compounds in similar contents in rocket leaves. Similar to phenolic acids, flavonoid synthesis was not enhanced at the beginning of the shelf life (5th day), although the stimuli of these compounds induced by lighting conditions was notorious after the 8 th day.…”
Section: Resultssupporting
confidence: 89%
“…Six different flavonoids with high antioxidant ability have been identified in rocket sprouts, from which quercetin reported the highest content followed by kaempferol derivatives (1,2,3, all of them attached to mono- and disaccharide sugars), rutin, and a quercetin derivative (attached to mono- or disaccharide sugars), while kaempferol was found in very low amounts ( Table 3 ), which agrees with those reported by Cuellar et al [ 28 ] and Schiavon et al [ 29 ], who found such compounds in similar contents in rocket leaves. Similar to phenolic acids, flavonoid synthesis was not enhanced at the beginning of the shelf life (5th day), although the stimuli of these compounds induced by lighting conditions was notorious after the 8 th day.…”
Section: Resultssupporting
confidence: 89%
“…Kaempferol 3,4'-diglucoside is the most abundant flavonol in EBuOH fraction because of the higher polarity of n-butanol than that of ethyl acetate. Flavonol di-glycosides are main components in EBuOH, EDW and crude 70% ethanol extract, which is consistent with the study in the past [26][27][28]. Total flavonol content is comparatively large in EEA (13.2%) and EBuOH (7.7%), which is positively related to the results of the total phenolic and flavonoid content as shown in Table 1.…”
Section: Analysis Of Flavonolssupporting
confidence: 90%
“…Kaempferol 3,4 ′ -diglucoside is the most abundant flavonol in the EBuOH fraction because of the higher polarity of n-butanol than that of ethyl acetate. Flavonol di-glycosides are the main components in EBuOH, EDW, and crude 70% ethanol extract, which is consistent with the studies in the past [26][27][28]. Total flavonol content is comparatively large in EEA (13.2%) and EBuOH (7.7%), which is positively related to the results of the total phenolic and flavonoid content, as shown in Table 1.…”
Section: Analysis Of Flavonolssupporting
confidence: 89%